2012
DOI: 10.1177/039463201202500318
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic Saline is More Effective Than Normal Saline in Seasonal Allergic Rhinitis in Children

Abstract: Allergic rhinitis (AR) is a very common childhood disease that is associated with a significant reduction in the patients' quality of life. Its treatment combines educating the patients and their parents, immunotherapy and drug administration. However, even the best approach does not relieve the symptoms of a number of patients. Alternative therapies are particularly needed for children because the fear of adverse events frequently reduces parental compliance to the prescribed drugs, and immunotherapy is less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(78 citation statements)
references
References 29 publications
3
73
0
2
Order By: Relevance
“…[12] found that family physicians in Wisconsin included children aged <7 years among the subjects eligible for NSI. The opinion of these physicians concerning the tolerability of NSI is similar to that of the primary care pediatricians enrolled in this study, and is supported by the data collected in other studies evaluating the effect of NSI on children [3-8]. The incidence of adverse events following NSI was usually very low, and most of the studies highlighted the fact that they were not severe enough to preclude continuing treatment.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…[12] found that family physicians in Wisconsin included children aged <7 years among the subjects eligible for NSI. The opinion of these physicians concerning the tolerability of NSI is similar to that of the primary care pediatricians enrolled in this study, and is supported by the data collected in other studies evaluating the effect of NSI on children [3-8]. The incidence of adverse events following NSI was usually very low, and most of the studies highlighted the fact that they were not severe enough to preclude continuing treatment.…”
Section: Discussionsupporting
confidence: 78%
“…A number of recent studies have shown that nasal saline irrigation (NSI), a practice widely used to treat upper respiratory tract diseases in adults [1,2], can also be effective in children with infectious and/or allergic respiratory problems not only as adjunctive treatment, but also alone [3-8]. NSI significantly reduces nasal secretions/post-nasal drip in children with chronic rhinosinusitis, and considerably improves radiographic signs of disease [3]; it also reduces the need for surgery even in patients resistant to medical treatment with antibiotics and nasal corticosteroids [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that hypertonicity can reduce mucosal oedema due to osmotic pressure-induced water transport through the epithelial membrane, improving mucociliary clearance [19]. Previous data reported the efficacy of nasal irrigation with hypertonic saline solution in children with AR [20,21].…”
Section: Discussionmentioning
confidence: 99%